Membangun Kesadaran Remaja Tentang Risiko Kehamilan di Luar Nikah Melalui Edukasi Kesehatan Reproduksi - Yanita Trisetiyaningsih; Masta Hutasoit; Afi Lutfiyati (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2026)
Adolescence is a vulnerable period for risky behavior, including premarital sexual intercourse, which can potentially lead to unwanted pregnancy (KTD). Comprehensive reproductive health education is considered an effective preventive strategy. This community service activity aims to improve the understanding of students at SMA Negeri 1 Gamping, Yogyakarta, and to evaluate the effectiveness of health education in increasing adolescent knowledge about preventing premarital pregnancy. The partner for this community service implementation was SMA Negeri 1 Gamping, Yogyakarta, with 29 12th-grade students participating. The program was implemented in October 2025 with 29 12th-grade students at SMA Negeri 1 Gamping (17 boys and 12 girls). This community service implementation was carried out in three stages: preparation, implementation, and evaluation. The preparation phase included obtaining a community service permit and preparing educational materials, posters, and educational videos on preventing premarital pregnancy. The intervention consisted of a single health education session covering reproductive health, the risks of premarital sexual intercourse, and prevention methods. The evaluation phase involved distributing a post-test questionnaire to assess respondents' understanding of premarital pregnancy prevention. Effectiveness was evaluated by comparing knowledge levels before and after the counseling. Before the education, 25 people (86.2%) had good knowledge, and 4 people (13.8%) had poor knowledge. After the education, this increased to 28 people (96.6%) having good knowledge and only 1 person (3.4%) having poor knowledge. These results indicate that health education significantly improved participants' knowledge. Health education has proven effective as an intervention to increase adolescents' understanding of premarital pregnancy prevention. Similar programs are recommended for sustainable and broader implementation in schools as part of adolescent health promotion and prevention efforts.